Bioaugmentation with existing potent microorganisms to accelerate the treatment efficacy of paper industry wastewater pollutants. Issue 5 (October 2021) - Sonkar, Madan; Kumar, Vivek; Kumar, Prasun; Shah, M.P.; Majumdar, C.B.; Biswas, J.K.; Dutt, Dharm; Mishra, P.K.
Abstract: Effluent discharged from paper industries has an unfavourable impact on all the biotic and abiotic components of the environment due to the presence of various bio-recalcitrant toxic compounds. Multiple physico-chemical treatment systems have been adopted over the last two decades for the elimination of refractory organics from paper industry effluent but with limited success. Augmentation of biological treatment through metabolic and cometabolic strategies seems to be a promising and sustainable option. This article aims at presenting a comprehensive account of treating the paper industry effluent with existing treatment strategy using potent green agents through bioaugmentation and mineralization of chlorophenols via ortho- and meta- pathways. Sequential treatment based on consortia of specialized microorganisms remove > 90% of different toxic and recalcitrant compounds present in paper industry effluent. The rapid technological development in microbial fuel cells holds the potential for simultaneous paper industry effluent treatment and energy production. Graphical Abstract: ga1 Highlights: Defined bacterial and fungal consortium in aid of bioaugmentation. Bioaugmentation strategies for efficient removal of recalcitrant organics. Cometabolism and metabolism as a tool against organic compounds in paper industry effluent. Sequential treatment as a novel approach in treatment of paper industry industrial effluent.